2019
DOI: 10.1002/lary.28067
|View full text |Cite
|
Sign up to set email alerts
|

The rising rate of nonsmokers among laryngeal carcinoma patients: Are we facing a new disease?

Abstract: Objectives/Hypothesis Laryngeal squamous cell carcinoma (SCC) is strongly associated with tobacco smoking. With the rising awareness of tobacco's adverse health effects, we have witnessed a global decrease in tobacco use. Nevertheless, laryngeal SCC remains prevalent and includes a subset of patients lacking the traditional risk factors. Study Design A two‐center retrospective cohort. Methods Medical records of patients diagnosed with laryngeal SCC between 2009 and 2016 were reviewed. Data collected included d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…A recent study of young patients with laryngeal cancer (<40 years old) has similarly shown that young patients are more likely to be female compared to older patients (33.6% vs. 19.6%) 9 . In addition, young patients were noted to have decreased supraglottic tumors and increased glottic tumors compared to older patients 9,17 . Prior laryngeal cancer studies have noted an association between nonsmokers and glottic tumors 17,18 and another study noted differences in the anatomic distribution of premalignant and malignant glottic lesions according to smoking status 19 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study of young patients with laryngeal cancer (<40 years old) has similarly shown that young patients are more likely to be female compared to older patients (33.6% vs. 19.6%) 9 . In addition, young patients were noted to have decreased supraglottic tumors and increased glottic tumors compared to older patients 9,17 . Prior laryngeal cancer studies have noted an association between nonsmokers and glottic tumors 17,18 and another study noted differences in the anatomic distribution of premalignant and malignant glottic lesions according to smoking status 19 .…”
Section: Discussionmentioning
confidence: 98%
“…A handful of other investigators have also highlighted the unique patient-and tumor-level characteristics of younger patients with laryngeal cancer and wondered if these findings pointed to a nontraditional disease etiology. 9,14,17,18 A recent study of young patients with laryngeal cancer (<40 years old) has similarly shown that young patients are more likely to be female compared to older patients (33.6% vs. 19.6%). 9 In addition, young patients were noted to have decreased supraglottic tumors and increased glottic tumors compared to older patients.…”
Section: Unique Characteristics Of Young Patients With Laryngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, androgen receptors showed significantly lower expression in poorly differentiated tumors and cancers with lymphatic invasion. Estrogen receptors B and progesterone receptors were thus considered as markers of aggressive tumor biology [14].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 The reported smoking rate among adults decreased by 25.8% from 20.9% in 2005 to 15.5% in 2016. 5 Moreover, the age-standardized mortality rate of alcohol-related LSCC decreased by 1.78% per year, whereas the death number has increased by 29.2% during the study period. 4 Overall, the 5-year relative survival rate improved from 52.7% to 65.9% for patients with head and neck cancers in recent years.…”
Section: Introductionmentioning
confidence: 88%